Perancangan Continuity Tester Pada Proses Pengkabelan Pesawat - Fauzia Haz; Arifil Fikri; Giri Angga Setia (Department of Electrical Engineering, UNJANI, 2021)
In the process of making aircraft, it requires strict standard requirements in accordance with the requirements that have been regulated in the world of aviation. One example is in the manufacture of a series of aircraft harness cables at the Harnessing Shop PT. Dirgantara Indonesia having many stages, including cable marking, looming, connection, continuity, insulation. Of course, for each stage is inspected. In continuity testing, it is done manually using a multimeter so it requires at least 3 people and the testing process is considered quite long. Given these problems, it is necessary to have a replacement multimeter in continuity testing to speed up and simplify the testing process. The continuity testing tool uses the Arduino Mega 2560, IC LM317T microcontroller, relay as the main component. The microcontroller is used to process the reading data according to the datasheet drawing, the LM317T IC is used to regulate the output voltage from the Arduino which will be converted to a resistance value, the relay is used to detect the position of the second end point in continuity testing. A user interface web browser is used to operate the tool and display data from the results of continuity testing. From the test results, it is found that the readings of the suitability of the installation point are in accordance with the actual cable harness and the resistance value is close to the same compared to using a multimeter. The passed statement will appear when the actual point reading of the cable harness is in accordance with the datasheet drawing, while the failed statement will appear when the actual point on the wiring harness does not match the datasheet drawing. The test results are in the form of excel data which can be easily stored by the operator.